The Uncovering of the Hidden Connection Between MAFLD and Cardiovascular Risk - Muhammad Amjad Khan, Shakeel Ahmad, Khatib Ul Islam, Muhammad Shahzad Hafeez, Shafaq Farooq, Muhammad Adil Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to determine the connection between MAFLD and cardiovascular risk. Methods: Total 224 patients were presented in this study. Participants in the study were chosen after they had undergone a thorough medical examination. Coronary artery calcium score (CACS), quantitative stenosis grade, coronary artery disease (CAD), and 10-year ASCVD risk were among the coronary risk surrogates that were examined in relation to fatty liver condition. SPSS 22.0 was used to analyze all data. Results: Among 224 cases, 137 (61.2%) were males and 87 (38.8%) were females. Patients mean age was 61.8 years and had mean BMI 26.8 kg/m2. Most common comorbidity was hypertension. Among all, 43 (19.2%) cases had previous history of CVD. We found independently association of MAFLD with CVD in multivariable analysis. Conclusion: Our results suggest that MAFLD may be a more accurate predictor of cardiovascular disease risk, and that fibrosis evaluation may be useful for more in-depth prognosis in MAFLD patients. Keywords: MAFLD, CVD, Hypertension